ANALYSIS OF ATTRACTION AND PURCHASE INTENTION ON PURCHASE DECISIONS OF TRADISONAL WOVEN PRODUCTS IN EAST OKU REGENCY - Reka Malinda; Winda Feriyana; Deviana Susanti (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
The attractiveness of consumer buying interest is an important thing in marketing, especially in the sale of traditional handicraft products, namely woven mats. The sustainability of production will continue if consumers continue to use these traditional products even in the midst of increasingly sophisticated technological advances that produce modern products. The purpose of the study was to analyze the attractiveness of consumers' buying interest towards the results of traditional handicraft products from woven mats. The method used is purposive sampling technique. Keywords: Buying interest, the production of traditional handicraft woven mats